Synthesis, antiproliferative activity in cancer cells and DNA interaction studies of [Pt(cis-1,3-diaminocycloalkane)Cl2] analogs - Hoeschele, James D; Kasparkova, Jana; Kostrhunova, Hana; Novakova, Olga; Pracharova, Jitka; Pineau, Paul; Brabec, Viktor (Journal of biological inorganic chemistry, 2020)
The search for more effective platinum anticancer drugs has led to the design, synthesis, and preclinical testing of hundreds of new platinum complexes. This search resulted in the recognition and subsequent FDA approval of the third-generation Pt(II) anticancer drug, [Pt(1,2-diaminocyclohexane)(oxalate)], oxaliplatin, as an effective agent in treating colorectal and gastrointestinal cancers. Another promising example of the class of anticancer platinum(II) complexes incorporating the Pt(1,n-diaminocycloalkane) moiety is kiteplatin ([Pt(cis-1,4-DACH)Cl2], DACH = diaminocyclohexane). We report here our progress in evaluating the role of the cycloalkyl moiety in these complexes focusing on the synthesis, characterization, evaluation of the antiproliferative activity in tumor cells and studies of the mechanism of action of new [Pt(cis-1,3-diaminocycloalkane)Cl2] complexes wherein the cis-1,3-diaminocycloalkane group contains the cyclobutyl, cyclopentyl, and cyclohexyl moieties. We demonstrate that [Pt(cis-1,3-DACH)Cl2] destroys cancer cells with greater efficacy than the other two investigated 1,3-diamminocycloalkane derivatives, or cisplatin. Moreover, the investigated [Pt(cis-1,3-diaminocycloalkane)Cl2] complexes show selectivity toward tumor cells relative to non-tumorigenic normal cells. We also performed several mechanistic studies in cell-free media focused on understanding some early steps in the mechanism of antitumor activity of bifunctional platinum(II) complexes. Our data indicate that reactivities of the investigated [Pt(cis-1,3-diaminocycloalkane)Cl2] complexes and cisplatin with glutathione and DNA binding do not correlate with antiproliferative activity of these platinum(II) complexes in cancer cells. In contrast, we show that the higher antiproliferative activity in cancer cells of [Pt(cis-1,3-DACH)Cl2] originates from its highest hydrophobicity and most efficient cellular uptake.
Keywords: cisplatina; platina; Glutathione; Hydrocarbons, Cyclic; DNA; nádorové buněčné linie; Cell Line, Tumor; Humans; permeabilita buněčné membrány; Cell Membrane Permeability; Pt(1,n-diaminocycloalkane) moiety; protinádorové látky; Cell Proliferation; cyklické uhlovodíky; Organometallic Compounds; organokovové sloučeniny; apoptóza; Drug Screening Assays, Antitumor; glutathion; Platinum; Cellular uptake; Cisplatin; Antitumor; Oxaliplatin; Antineoplastic Agents; lidé; screeningové testy protinádorových léčiv; Apoptosis; proliferace buněk